Evaluation about the relationships of power, stateand education - Rodríguez Arboleda, Fernando (2020)
Relations among Power, State and Education uncover the opposite existing materially and the theoretical considerations of the essential content of power. From the dialectical point of view, the implications of the power existence in the State apparatus are explained, being a domination and control organ,which exerts the power and its capacity to handle the State and the education as a transmission tool of the dominant culture inhistory. Education is part of a complex reality linked to economic, political, legal processes in which the State is a modern business administrator and the education is subjected to the market laws. On the other hand, education reveals the alienation that without being exclusive of capitalism is the main enemy of the human being, so awareness should be taken towards a critical resistance, which allows to consolidate an independent, autonomous and solidarity formation. The aim of the article is to explain the relation among power, State and education, as well as the conditions of the production of knowledge and the social purpose, and above all who controls it, since there is a direct relation in knowledge/power as an extension, and the relation with the social inequities in which the State is the unconditional guarantor. The article is written in a chronological way to study the liberal, conservative State which appears at the beginning of the XX century; later to the developmental State which arises in thesixties of this century and during the application of the neoliberal model.